GENERAL CHARACTERISTICS OF CONVERSION AS A MEANS OF WORD BUILDING (ON THE BASIS OF THE RUSSIAN AND FRENCH LANGUAGES) (Proceedings of Southern Federal University. Philology, 2012)
Pshenichnaya A. Y.Keywords: conversion in word building, universal features, typological features, synchronic and diachronic aspects.The article is devoted to the existing approaches in modern linguistics to the interpretation of conversion in word building. The Russian and French languages have different language structures. That fact enables to specify the universal features of conversion as a word building means. This word formation process is viewed from synchronic and diachronic aspects.